PEPATAHAN DAN UNGKAPAN DALAM BAHASA BATAK ANGKOLA (Kajian Metabahasa Semantik Alami) - Syahnan Daulay (Jurnal Edukasi Kultura: Jurnal Bahasa, Sastra dan Budaya, 2020)
Abstract Angkola Batak Language (BBA) is one of the regional languages that is still actively used by its speakers. In BBA there is a genre of language use known as proverbs and expressions. The proverbs and expressions in the BBA are known as natural language use genres which can also be found in various languages. Proverbs and expressions are universal lingual phenomena that are realized differently in various cultures. By applying the Natural Semantic Meteoric Approach (MSA), this paper describes the reflection of meaning in the proverb and BBA expressions that describe the universality and uniqueness, as well as the dynamics of its use by the Batola Angkola community which is compared with similar forms in Indonesian. Based on the results of the study it was concluded that the meaning of the proverbs and expressions in BBA is a cultural product of universal language use. The lingual facts used to compose the proverbs and expressions in the BBA show the phenomenon of universal language cultural meaning. That every language has lingual forms which are universal cultural language phenomena is also found in the proverb and BBA expression.  Keywords: maxim, expression, Angkola Batak language